2013
DOI: 10.1016/j.watres.2013.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Source identification of nitrous oxide on autotrophic partial nitrification in a granular sludge reactor

Abstract: Emission of nitrous oxide (N 2 O) during biological wastewater treatment is of growing concern since N 2 O is a major stratospheric ozone-depleting substance and an important greenhouse gas. The emission of N 2 O from a lab-scale granular sequencing batch reactor (SBR) for partial nitrification (PN) treating synthetic wastewater without organic carbon was therefore determined in this study, because PN process is known to produce more N 2 O than conventional nitrification processes. The average N 2 O emission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 48 publications
4
82
2
Order By: Relevance
“…The N 2 O emission quantity per cycle varied from 3.33 to 7.76 mg (5.98 mg on average), accounting for 0.556%e1.29% (0.997% on average) of influent nitrogen. Fluctuation of the N 2 O emission quantity was also observed by Rathnayake et al (19). It might be due to fluctuation of airflow and hydraulic flow rates.…”
Section: Performance Of the Sbrsupporting
confidence: 55%
“…The N 2 O emission quantity per cycle varied from 3.33 to 7.76 mg (5.98 mg on average), accounting for 0.556%e1.29% (0.997% on average) of influent nitrogen. Fluctuation of the N 2 O emission quantity was also observed by Rathnayake et al (19). It might be due to fluctuation of airflow and hydraulic flow rates.…”
Section: Performance Of the Sbrsupporting
confidence: 55%
“…When the aeration rate was above 0.6 L/min, the N2O emission factor was below 1%, while when the nitrifier activity was low, it reached the highest ratio of 26.1%. Rathnayake et al [4] reported that the N2O emission factors to the influent NH4-N loading rate or to the removal of NH4-N during nitritation were 0.8% and 1.5%, respectively. However, Desloover et al [3] found that the N2O emission factor was in the range of 5.1%-6.6%.…”
Section: Effect Of Aeration Rates On N2o Emission During Nitrificationmentioning
confidence: 99%
“…If external organic carbon is dosed for denitrification, the operating cost will increase significantly. Therefore, novel processes, such as SHANRON, short-cut nitrification and anaerobic ammonium oxidation, and so on, have been developed to treat high ammonium containing wastewater [3,4]. The prerequisite of these processes is to achieve short-cut nitrification, namely nitritation (nitrifying ammonium to nitrite rather than nitrate).…”
Section: Introductionmentioning
confidence: 99%
“…After that, most of these studies have focused on the emissions of N 2 O in partial nitrification aerobic granular sludge systems for treating high strength ammonium wastewater (13e15). The relative contributions of the three pathways (hydroxylamine oxidation, nitrifier denitrification and heterotrophic denitrification) to N 2 O emissions in these systems were also quantitatively examined (9,15). The removal of nitrogen via nitrite is energy-and costefficient compared to conventional processes over nitrate.…”
mentioning
confidence: 99%